Membangun Framework Konseptual Terintegrasi Menggunakan Metode Composite Logic untuk Cloud Forensic Readiness pada Organisasi - Merisa Kurniasari Fadilla; Bambang Sugiantoro; Yudi Prayudi (STMIK Budi Darma, 2022)
In the Forensic Readiness approach, incident readiness is the goal of the company or organization in dealing with incidents that may occur. Forensic Readiness can consist of actions or steps, technical and non-technical, that supposedly maximize an organization's ability to use digital evidence. A well-built Cloud Forensic Readiness Framework can help speed up and simplify decision-making regarding an incident occurring in a cloud computing environment. This creates new opportunities for collaboration in the field of digital forensics and cloud computing or cloud computing, so that solutions can be studied and researched by analyzing various literature sources of cloud computing forensic readiness framework and building an integrated cloud forensic readiness framework on an institutional scale using the composite logic method. With the completeness of the readiness framework designed, it is a kind of research that is expected to ease decision making process for organizational stakeholders to handle incident responses.